Students’ problem-solving skills in HOTS geometry tasks: A case study of spatial ability - Musa, Lisa Aditya Dwiwansyah; Munir, Nilam Permatasari; Muhammad Ikram; Javier Garcia Garcia; Camilo Andres Rodriguez-Nieto (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to analyze the problem-solving processes of students with high spatial ability when solving geometry problems based on Higher Order Thinking Skills (HOTS). The research was motivated by the persistently low performance of Indonesian students in international assessments such as PISA and TIMSS, highlighting the need to explore cognitive factors that underpin HOTS, particularly spatial reasoning. Method: A qualitative descriptive approach was employed. Two students with high spatial ability were selected through a snowball sampling technique, based on spatial ability test results and teacher recommendations. Data were gathered through unstructured interviews and classroom observations, focusing on how the participants approached and solved HOTS-based geometry problems. The collected data were analyzed through three stages: data reduction, data display, and conclusion drawing. Findings: The findings show that students with high spatial ability demonstrate effective visualization and reasoning processes that enable them to comprehend problem statements, identify relevant information, and design appropriate strategies for solving HOTS-based geometry problems. They can implement their strategies accurately, evaluate their reasoning, and justify their conclusions confidently. Significance: This study underscores the pivotal role of spatial ability in fostering students’ Higher Order Thinking Skills in geometry learning. The findings suggest the need to incorporate spatial reasoning tasks into mathematics instruction and to design HOTS assessment instruments that account for students’ spatial cognitive profiles.